Reversible cardiomyopathy in a patient with Marfan’s syndrome. Case report - Viñas-Mendieta, Adriana E. (2023)
Marfan´s syndrome is a multisystemic, autosomal dominant congenital abnormality of variable penetrance that affects the integrity of connective tissue. In the cardiovascular system, the dysfunction of the physiology of the aortic root and the myocardial fibrosis originates non-ischemic cardiomyopathy independent of valve lesions. Few data have been reported on the prevalence of arrhythmias and its impact on heart function. We present a 21-year-old man with Marfan’s syndrome and heart failure with frequent supraventricular arrhythmias and aortic root dilation. After ablation in the posteroseptal area of the mitral ring and Tirone David Surgery, there was clinical improvement, the left ventricular ejection fraction increased dramatically from 33% to 46%, the left ventricular end-diastolic volume decreased from 90 ml/m2 to 77 ml/m2 and the NT-proBNP decrease from 1100 pg/mL at 180 pg/mL.